Effects of seat tray table height and body anthropometry dimensions on passengers' in-flight comfort - Hamil, Muhamad Hafiz Fathullah; Romli, Fairuz Izzuddin; Muhammad Shafiq Reincastle, Muhammad Shakir Reincastle (Praise Worthy Prize, 2023)
In-flight sitting comfort has become a key selection criterion for aircraft passengers when choosing their travel options among available flight services. This comfort feeling can often be associated with the ease of passengers in performing their typical in-flight activities. In view of this notion, having an appropriate height of the seat tray table that aptly matches the passengers body anthropometry is imperative to enable them to adopt comfortable sitting posture while doing their in-flight activities. In this study, an activity-based sitting comfort experiment is conducted in an aircraft cabin mock-up where the participants were asked to rate their comfort level when they used the seat tray table during eating, writing and typing activities at seven different settings of the tray tables height: 66 cm, 69 cm, 72 cm, 75 cm, 78 cm, 81 cm and 84 cm. A total of 15 volunteers participated in the experiment and the collected sitting comfort data is then statistically analyzed through ANOVA method using the MINITAB software. The analysis results have indicated that the height of seat tray table and several passengers anthropometry parameters have high influences on their in-flight comfort level while performing their common in-flight activities. Additionally, the findings also suggested that there is a potential optimum setting of seat tray tables height that can maximize the passengers comfort level.